EFFECT OF TRUNK DISSOCIATION RETRAINER" IN IMPROVING REACHING CAPACITY IN HEMIPLEGICSUBJECTS - ARUNACHALAM RAMACHANDRAN,; ANANDH VAIYAPURI,; L.CHANDRASEKAR, (International Journal of Pharma and Bio Sciences, 2016)
This study aims to find the effectiveness of “trunk dissociation retrainer” for improving trunk performance and functional activities in hemiplegia. A total of 156 hemiplegic subjects from both genders, who were aged between 40 to 75 years, who scored 6 or more in trunk impairment scale were randomly assigned to three groups by random number method with 52 in each group. “Trunk dissociation retrainer” group received training using the new tool “Trunk Dissociation Retrainer” and conventional exercises, the MTD group received manual trunk dissociation training and conventional exercises, the control group received only the conventional exercises. Duration of intervention was 60 minutes per day, three days a week, for four weeks. Functional reach test was used to measure the outcome using a blinded evaluator. The results of the study showed that there was a significant improvement in reaching in TDR group compared to the other two. There were no significant difference in improvement between the MTD and the control group. This study concludes that trunk dissociation retrainer can be a better tool for training trunk dissociation. Training in Trunk dissociation retrainer results in a significant improvement of functional reaching capacity in subjects with hemiplegia.